A Pragmatic Diplomat in Pluralization: Yoshio Okawara and the Restoration of Postwar Japan–US Relations. (3rd July 2018) - Chijiwa, Yasuaki
Abstract : In this article, the author will focus on the role former Japanese diplomat Yoshio Okawara played in the "restoration" in the context of postwar Japan–US relations, particularly in his capacity as Japan's ambassador to the US. During the 1980s, a period when trade friction between Japan and the US was particularly intense, and diplomatic relations pluralized, Okawara emerged as a "pragmatist, " striving to vanquish the "perception gap" between the two nations. Today, the Donald J. Trump administration seems to be shaking up the global system of free trade. In the current situation, there is much to learn from the example set by the diplomat Okawara, a pragmatist who throughout his life did so much to narrow the perception gap that caused the trade frictions of the 1980s and to restore the Japan–US relationship that had been ravaged by war.